The role of fibromodulin in inflammatory responses and diseases associated with inflammation - Zhao, Feng; Bai, Yang; Xiang, Xuerong; Pang, Xiaoxiao (Frontiers in Immunology, 2023)
Inflammation is an immune response that the host organism eliminates threats from foreign objects or endogenous signals. It plays a key role in the progression, prognosis as well as therapy of diseases. Chronic inflammatory diseases have been regarded as the main cause of death worldwide at present, which greatly affect a vast number of individuals, producing economic and social burdens. Thus, developing drugs targeting inflammation has become necessary and attractive in the world. Currently, accumulating evidence suggests that small leucine-rich proteoglycans (SLRPs) exhibit essential roles in various inflammatory responses by acting as an anti-inflammatory or pro-inflammatory role in different scenarios of diseases. Of particular interest was a well-studied member, termed fibromodulin (FMOD), which has been largely explored in the role of inflammatory responses in inflammatory-related diseases. In this review, particular focus is given to the role of FMOD in inflammatory response including the relationship of FMOD with the complement system and immune cells, as well as the role of FMOD in the diseases associated with inflammation, such as skin wounding healing, osteoarthritis (OA), tendinopathy, atherosclerosis, and heart failure (HF). By conducting this review, we intend to gain insight into the role of FMOD in inflammation, which may open the way for the development of new anti-inflammation drugs in the scenarios of different inflammatory-related diseases.